Every crooked nanny eaudiobook - Andrews, Mary Kay (Callahan Garrity, 2013)
"Fresh, confident, intelligent and amusing. Grab a cold drink, put your feet up, and enjoy yourself."— Sue Grafton The first entry in a thoroughly original and witty series that sets Atlanta house cleaner cum sleuth Callahan Garrity on the trail of a client's missing au pair, now published under the name Mary Kay Andrews for the first time. Callahan Garrity is the owner of House Mouse, a cleaning service that tidies up after Atlanta's elite. She's also a former cop and a part-time sleuth, and she and her coterie of devoted helpers can ransack a house for clues faster than it takes a fingerprint to set. Callahan is on the job when her client announces that her pretty, nineteen-year-old Mormon nanny has disappeared—along with jewelry, silver, and some sensitive real-estate documents. Soon Callahan and her crew of eccentric cleaners are involved in a job messier than any they've ever encountered. Illicit love triangles, crooked business deals, long-distance scams— it's going to require some industrial-strength sleuthing on Callahan's part to solve this one.